Organocatalytic Approach for the Synthesis and Biological Studies of Naphthalene Fluorescent Probe through Hydrogen Transfer Reaction. Issue 46 (12th December 2022) - Sau, Madan; Dubey, Sapana; Sahoo, Jigyansa; Sahoo, Gokarneswar; Trivedi, Pragya; Jana, Avijit; Samanta, Subhankar; Das, Tapas
Abstract: Herein we report an organocatalytic synthesis of highly fluorescent naphthalene derivatives through hydrogen atom transfer featuring neat and mild reaction conditions under air with high substrate tolerance along with atom economy by the unprecedented use of DBU, where oxidation and reduction occurred in one‐pot. Synthesized compounds are utilized in photophysical studies, cytotoxic studies and cell imaging studies of colon cancer cell line CT26. Abstract : A remarkably effective, eco sustainable solvent‐free method has been reported for the Hydrogen transfer to produce a fluorescent aromatic compound with satisfactory to good yields. This methodology covers a wide range of substrates, and the synthesized compounds have superior fluorescence properties, so the photophysical and biological properties are investigated.